Digitalisasi UMKM Desa melalui Pelatihan AI dan Pemasaran TikTok Shop - fidyah yuli ernawati, fidyah; hendrayanti, Silvia; Nindhita, Yoga (CITAKARYA Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy. Based on data from the Ministry of Cooperatives and SMEs, MSMEs contribute more than 60% to the national GDP and absorb around 97% of the workforce (Kemenkop UKM, 2023). However, the majority of MSMEs in rural areas still face major challenges in terms of digitalization, market access, and technology utilization. One of the popular digital platforms is TikTok Shop, which allows MSMEs to market their products more widely through short video content. Training on the use of TikTok Shop has been proven to help MSMEs increase sales and expand market reach (Arum & Hidayat, 2023). TikTok Shop as an e-commerce platform based on short videos is becoming a new trend in digital marketing strategies. Its massive use by the younger generation opens up great opportunities for MSMEs to enter a wider market at a relatively low cost. With a combination of AI training (such as the use of chatbots for customer service or simple sales data analysis) and the use of TikTok Shop, village MSMEs can increase their business scale sustainably. The implementation of community service was carried out in Karangtengah Village, Demak. The problem raised in this PKM is to increase the scale of marketing based on technology or online media, encouraging people to increase their knowledge, skills, and awareness in utilizing the TikTok Shop application to improve digital marketing.